Pengaruh Self Efficacy, Kecerdasan Emosional, Kepemimpinan Terhadap Kinerja Pegawai Sekretariat Daerah Provinsi Kepulauan Riau Melalui Dengan Organization Citizenship Behaviour - Nurhayati; Wibisono , Chablullah (Bahtera Inovasi, 2024)
Employee performance is how employees contribute to the organization, both in terms of absence at work, quality of work, quantity of work period and attitude in the organizational environment. The purpose of this study was to determine the effect of self-efficacy through organizational citizenship behavior on employee performance at the Regional Secretariat of the Riau Islands Province. To determine the effect of emotional intelligence through organizational citizenship behavior on employee performance at the Regional Secretariat of the Riau Islands Province. To determine the effect of leadership through organizational citizenship behavior on employee performance at the Regional Secretariat of the Riau Islands Province. The research method is quantitative, using Structural Equation Modeling abbreviated as SEM, a multivariate analysis method that can be used to describe the relationship of linear relationships simultaneously between observation variables (indicators) and variables that cannot be measured directly (latent variables). SEM is a multivariate statistical analysis method. Based on the study, it was found that Self Efficacy with the mediation of Organization Citizenship Behavior can have a significant effect on performance at the Regional Secretariat of the Riau Islands Province. Emotional Intelligence with the mediation of Organization Citizenship Behavior can have a significant effect on performance at the Regional Secretariat of the Riau Islands Province. Leadership with Organization Citizenship Behavior mediation cannot have a significant effect on performance at the Regional Secretariat of the Riau Islands Province.